Decoding tRNA dynamics in neuroimmune disorders: mechanistic insights, diagnostic innovations, and therapeutic opportunities - Liang, Enlin; Wang, Wenya; Zhang, Li (Frontiers in Immunology, 2025)
Transfer RNA (tRNA) and its derivatives, once regarded solely as translational adaptors, are now recognized as pivotal regulators of neuroimmune homeostasis. Dysregulated tRNA biogenesis, stress-induced fragmentation, and chemical modifications are increasingly implicated in the pathogenesis of neuroinflammatory and neurodegenerative disorders, including multiple sclerosis, neuromyelitis optica spectrum disorder, Alzheimer’s disease, and Parkinson’s disease. This review synthesizes emerging evidence on tRNA-derived small RNAs (tsRNAs), tRNA-modifying enzymes, and mitochondrial tRNA variants as drivers of immune dysregulation, glial activation, and neuronal injury. We highlight innovative diagnostic biomarkers (e.g., plasma tsRNAs, aminoacyl-tRNA synthetase-interacting multifunctional protein 1) and therapeutic strategies targeting tRNA modification pathways (e.g., queuine analogs, tRNA ligase inhibitors). By bridging tRNA biology with neuroimmunology, this work underscores the translational potential of tRNA-centric approaches in managing complex neurological diseases.